O-023 Stent-assisted coiling of cerebral aneurysms: multi-center analysis of radiographic and clinical outcomes in 659 patients. (22nd July 2019) - Mokin, M; Primiani, C; Piper, K; Fiorella, D; Rai, A; Orlov, K; Kislitsin, D; Gorbatykh, A; Mocco, J; DeLeacy, R; Lee, J; Spiotta, A; et al.
Abstract : Introduction: Endovascular stent-assisted coiling approach for the treatment of cerebral aneurysms is evolving rapidly with the availability of new stent devices. It remains unknown how each type of stent affects the safety and efficacy of the stent-coiling procedure. Methods: This study compared the outcomes of endovascular coiling of cerebral aneurysms using Neuroform (NEU), Enterprise (EP), and Low-profile Visualized Intraluminal Support (LVIS) stents. Patient characteristics, angiographic results using the Raymond-Roy grade scale (RRGS), clinical outcomes and procedural complications were analyzed in our study. Results: 659 patients with 670 cerebral aneurysms treated with stent-assisted coiling (NEU, n=182; EP, n=158; LVIS, n=330) were retrospectively collected from six academic centers. Patient characteristics included mean age 56.3±12.1 years old, female prevalence 73.9% and aneurysm rupture on initial presentation of 18.8%. We found differences in complete occlusion on baseline imaging, defined as RRGS I, among the three stents: LVIS 64.4%, 210/326; NEU 56.2%, 95/169; EP 47.6%, 68/143; p=0.008. The difference of complete occlusion on 10.5 months (mean) and 8 months (median) angiographic follow-up remained significant: LVIS 84%, 251/299; NEU 78%, 117/150; EP 67%, 83/123; p=0.004. There were 7% (47/670) intra-procedural complications and 11.5% (73/632) post-procedural related complications in our cohort. Conclusions: The type of stent used for stent-assisted coiling affects immediate and long-term angiographic outcomes. Randomized prospective trials comparing the different types of stents are warranted. Disclosures: M. Mokin: 2; C; Toshiba (Canon) Medical. C. Primiani: None. K. Piper: None. D. Fiorella: 1; C; reports grants, non-financial support, and other funding from Penumbra, Cerenovus, and Stryker; non-financial support and other funding from Genentech and Shape Memory Medical; and grants from Siemens. A. Rai: 6; C; reports other from Penumbra; and non-financial support from Microvention and Stryker. K. Orlov: None. D. Kislitsin: None. A. Gorbatykh: None. J. Mocco: 6; C; reports other from Penumbra, Cerebrotech, Rebound Therapeutics, TSP, Lazarus Effect, Medina, Pulsar Vascular, and Blockade. R. DeLeacy: 6; C; reports other and non-financial support from Penumbra; and non-financial support from Cerenovus and Siemens. J. Lee: None. A. Spiotta: 6; C; reports other and non-financial support from Penumbra, Pulsar Vascular, and Stryker and grants, other, and non-financial support from Microvention. R. Turner: 2; C; consultant for Penumbra, Medtronic, Microvention, Codman, Pulsar Vascular, Q'Apel, Rebound Medical, and Blockade Medical. I. Chaudry: 6; C; reports other, grants, and non-financial support from Penumbra and Pulsar Vascular; grants and non-financial support from Medtronic, Microvention, and Codman; non-financial support and other from Bloc. A. Turk: 6; C; reports other, grants, and non-financial support from Penumbra and Pulsar Vascular; grants and non-financial support from Codman, Microvention, and Medtronic; non-financial support and other from Bloc.